ANALISIS RASIO LIKUIDITAS, SOLVABILITAS, DAN PROFITABILITAS PADA PT TELKOM INDONESIA TBK PERIODE 2020-2024 - Salsabilla Hanik Nur Abidah; Featy Octaviany (JURNAL LENTERA AKUNTANSI, 2026)
Financial ratio analysis is a method used to analyze a company's financial condition and performance by comparing one account with another account in the financial statements. The background of this study is to determine the condition of the company's financial statements as well as the liquidity, solvency, and profitability ratios. The research method used is a quantitative descriptive method, namely data that presents information about the amount or magnitude of a variable in the form of numbers or quantities in the form of financial statements for the period 2020 - 2024 at PT Telkom Indonesia Tbk. The data analysis method used is the horizontal analysis method, an analysis carried out by comparing financial statements for several periods. From the calculation results, it can be concluded that the liquidity ratio of PT Telkom Indonesia (Persero) Tbk in the period 2020 to 2024 only has a cash ratio that is in accordance with the ratio assessment score stated in the BUMN KMK with an assessment score of 5, and Telkom's quick ratio has a ratio value greater than the ratio value of PT Indosat Ooredoo Hutchison Tbk (ISAT). In terms of solvency ratios, Telkom's DAR and DER ratios are smaller than Indosat's ratio value, while Telkom's long-term debt to equity ratio in the period 2020 to 2024 has a ratio value smaller than Indosat's ratio value. In terms of profitability ratios, Telkom's ROA in the period 2020 to 2024 has a ratio value greater than Indosat's ratio value and ROE in all periods is in accordance with the ratio assessment score stated in the BUMN KMK with an assessment score of 20.